Creating partnerships between veterinarians and underserved producers: getting started with establishing veterinary client–patient relationships - Ritter, Nicola L.; Whitaker, Torri; Gonzales, Molly; Mays, Glennon; Washburn, Kevin Eugene; Posey, Richard D. (Frontiers in Veterinary Science, 2025)
ObjectivesTo provide local veterinarians and producers opportunities for collaboration and applied education related to the Veterinary Client Patient Relationship (VCPR); to assess the effectiveness of such opportunities in enhancing VCPR knowledge and confidence; and to establish VCPRs in hopes of improving economic efficiency and sustainability of small to medium-sized livestock operations.Materials and methodsTwo one-day “Creating Partnerships” workshops utilized educational resources in five learning sessions focused on communication, establishing a Veterinarian Client-Patient Relationship (VCPR), and telemedicine. A pre- and post-test, comprised of closed-ended and Likert scale questions, measured the workshops’ effectiveness in increasing knowledge and confidence related to veterinary and producer partnerships.ResultsPre- and post-test scores indicate significant increases in knowledge and confidence related to Veterinary Client-Patient Relationships. Twenty-seven percent of participants established a Veterinary Client-Owner-Patient Relationship (VCPR) with their local veterinarian following the workshops.DiscussionTargeted educational outreach shows promise in creating and maintaining veterinarian-producer relationships. Knowledge gains and attitude shifts related to Veterinary Patient Client Relationships may improve animal health outcomes, resulting in more sustainable and profitable livestock operations and veterinary practices.